Effect Of Supplementation Of Aloe Vera Extracts On Growth Performance In Commercial Broilers - Jagadeeswaran, A.; Selvasubramanian , S.; Chandrasekaran , D. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
An experiment was conducted in commercial broilers to study the effect of supplementation of Aloe vera (crude and standardized) extracts on growth performance. The data on growth parameters (weekly body weight, weekly body weight gain, cumulative feed consumption and feed conversion ratio) were analyzed. The results of the study revealed that the Aloe vera supplemented groups gained higher body weights than untreated group. Aloe vera crude extract supplemented group consumed more feed than other groups with resultant poor FCR. Aloe vera standardized extract supplemented group showed better FCR.
Keywords: Aloe vera; Broilers; rowth performance